(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Lichen is in a separate division in plant kingdom because of its symbiotic association and complex nature of an algae and fungi. Several lichen species are reported to be used tradiationally in many theraupatic practices. Many lichen species are reported as sources of several bioactive natural compounds. In this article, Roccella montagnei is evaluated for its potential antimicrobial activity. The crude extract obtained from the lichen thalli was subjected to preliminary phytochemical analysis and was exhibited the presence of various phytoconstituents. Antibacterial activity was investigated by disc diffusion method against selected bacterial pathogens and the extract exhibited significant activity which was revealed by valid inhibition zone formation.